SYNTHESIS OF ZEOLITE FROM DIATOM NAVICULA SP. BIOSILICA - Soim, Mohammad
Zeolites are crystalline microporous aluminosilicate materials with pore diameter less than 2 nm. Synthetic zeolites are generally synthesized from commercial silica sources such as TEOS (Tetraethylorthosilicate) which are quite expensive. Therefore, research on the synthesis of zeolite from the silica raw material needs another breakthrough to achieve an economical route. Diatoms can be used as promising material on zeolite synthesis because of highly silica content on their cell walls and their abundance in the nature. In this study, the synthesis of zeolites was done by using diatom Navicula sp. biosilica as natural resource, TEOS, and mixture of TEOS:biosilica. Firstly, diatoms purification process used HCl solution and calcination of biosilica pellet at 700 oC for 6-8 hours. Second, zeolite synthesis was done by hydrothermal treatment at 150 °C for 72 hours with molar ratio 1 SiO2:0,02 Al2O3:61 H2O:0,104 NaOH:0,12 TPA. XRD results showed that high crystallinity zeolites were successfully synthesized from diatom Navicula sp. biosilica and TEOS and have similarity of XRD pattern with ZSM-5. SEM results showed that the zeolite made from biosilica has two different morphology. However, zeolite that was synthesized from TEOS has spherical morphology.